A performance optimisationbased eCVT design method and analysis of representative HEV/PHEV powertrains. (27th December 2011) - Zhou, Leon; Dong, Zuomin
An electronically controlled continuous variable transmission (eCVT) which consists of planetary gears and electric machines plays a key role in advanced hybrid powertrains of HEV/PHEV/EREVs. Design of these eCVTs for best performance is a challenging task due to the complexity of these eCVTs and hybrid powertrain system derived from them. In this work, a performance modelling and optimisationbased design method is introduced to automatically identify the best performance of an eCVT or other complex hybrid vehicle powertrain system. The complex design optimisation problem for peak powertrain performance is solved using a unique twostage search method to significantly reduce needed computation and assure the accuracy of the optimisation. Four representative eCVT powertrain designs of representative HEV/PHEV/EREVs were used as case studies. Test results are calibrated using verified data to reveal the performance characteristics and potential of each powertrain designs. Application of this method to produce new eCVT and geartrain designs with enhanced performance is demonstrated.